2015
DOI: 10.1007/s11104-015-2635-x
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal inoculation and nitrogen fertilization affect the physiology and growth of spring wheat under two contrasting water regimes

Abstract: Aims Most plants benefit from mycorrhizal symbiosis through their improved abilities to take up nutrients and water. Information on the interactive effects of fungal inoculation, nitrogen (N) fertilization and drought on water use efficiency (WUE) and productivity of Canadian wheat varieties is scanty. Methods In this study, we investigated the effects of arbuscular mycorrhizal fungi (AMF) inoculation, N fertilization and water regime (well-watered (WW) vs water-deficit (WD)) on WUE, phosphorus (P) and N uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Previous studies also demonstrated that the degree of mycorrhizal symbiosis is intimately linked to plant water‐use efficiency (WUE; Querejeta et al . ; Zhang, Chang & Anyia ). WUE is defined as the amount of C acquired per unit of water transpired, reflecting the trade‐off between C gain and water loss.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies also demonstrated that the degree of mycorrhizal symbiosis is intimately linked to plant water‐use efficiency (WUE; Querejeta et al . ; Zhang, Chang & Anyia ). WUE is defined as the amount of C acquired per unit of water transpired, reflecting the trade‐off between C gain and water loss.…”
Section: Introductionmentioning
confidence: 99%
“…; Hobbie & Colpaert ) and herbaceous species (Al‐Karaki ; Omirou, Ioannides & Ehaliotis ; Zhao et al . ; Zhang, Chang & Anyia ). Beneficial associations with AM fungi might explain the resistance of subordinate species to drought but this has not been directly tested.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drought stress (DS), one of most predominant abiotic stresses, often results in an evident decrease in crop productivity and growth throughout the world (Zhang et al, 2016). Drought stress causes the damage to net photosynthetic behavior, electron transport system, and oxidative burst (Saraswathi and Paliwal, 2011).…”
Section: Introductionmentioning
confidence: 99%